Comparative Laparoscopic Cholecystectomy in Acute Cholecystitis in DHQ Abbottabad, KP-Pakistan - Ibrar Ahmed, Ajmal Khan, Faryal Saeed, Kamran Khan, Marium Khurshid, Saa Israf, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Early laparoscopic cholecystectomy before 72 hours is ideal for the treatment of acute cholecystitis after 72 hours, acute or ongoing fibrosis presents careful issues. Aim: To compare the results of an acute cholecystitis blood pressure monitoring center and a specialist acute surgical service 72 hours after symptoms. Study design: Cross-sectional study. Place and duration of study: Department of General Surgery Benazir Bhutto Shaheed Hospital, (DHQ) Abbottabad from 1st October 2021 to 30th March 2022. Methodology: One hundred and eighty acute cholecystectomy patients who went through CEL were enrolled. Record was gathered which included postoperative confusions, length of medical clinic stay, and season of a medical procedure. To get comparable outcomes, subgroup examination of older patients was performed. Results: Eighty operations were performed within 72 hours of symptoms and 100 operations were performed after 72 hours, Patients who received early laparoscopic cholecystectomy for more than 72 hours had longer complication-free time” (125.4 vs. 116 minutes, P=0.035) and hospital stay (4.59 vs. 3.09 days, P=0.001). Postoperative sampling was higher in patients older than 75 years (P < 0.001). Conclusion: Acute cholecystitis patients going through CLE in a careful unit might accomplish improved results even following 72 hours of side effects. In a subset of older patients, extensive hemostasis ought to be performed. Keywords: Acute cholecystitis, early laparoscopic cholecystectomy (ELC)